EFFECT OF TEMPERATURE DIFFERENCE ON HATCHING EGGS OF GREEN TURTLE (Chelonia mydas) - Ikhsan Setiawan; Efriyeldi '; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The purpose of this research was to know the condition of nesting beaches favored by green turtles (Chelonia mydas) and the effect of incubation temperature (heating source from incandescent) towards the incubation and hatching rate success. This research was conducted in October to December 2016 at the Turtle Breeding Facility at Jemur Island. This research used survey and experiment method. The research showed that the safe nesting ground with some vegetation on location I and the least predator at the location II, the wide beach area, and sloping beach with fine sand which making it easier for green turtles in digging the nest. These conditions were the reasons why green turtles choose Jemur Island as their nesting ground. Incubation temperatures effects the hatching rate success and hatching time of sea turtle’s eggs. The treatment that has the highest hatching rate is a 25 Watt light with average temperatures of 29.7oC which is 83.33%. Treatment using a 25 Watt light is the best treatment, with a highest numbers of hatching rate and has the fastest hatching time. Keywords: Hatching Egg turtle, Chelonia mydas, Jemur Island